2012
DOI: 10.1161/circinterventions.111.963876
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Elevated Baseline Troponin in Patients With Acute Coronary Syndromes and Chronic Kidney Disease Treated With Different Antithrombotic Regimens

Abstract: Background-Elevation of baseline cardiac troponin in patients presenting with acute coronary syndromes (ACS) confers an adverse prognosis. The prognostic value of troponin elevation in patients with chronic kidney disease (CKD) and ACS is less certain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…No significant difference was observed in Troponin I level between patients with or without development of arrhythmia, conduction defect and death (p>0.05). These observations are in consistent with the findings of the trial by Acharji [15][16][17] . Diderholm et al (2002) observed that troponin I level is an effective prognostic marker and its level predicts in-hospital out come in NSTEMI.…”
Section: Discussionsupporting
confidence: 93%
“…No significant difference was observed in Troponin I level between patients with or without development of arrhythmia, conduction defect and death (p>0.05). These observations are in consistent with the findings of the trial by Acharji [15][16][17] . Diderholm et al (2002) observed that troponin I level is an effective prognostic marker and its level predicts in-hospital out come in NSTEMI.…”
Section: Discussionsupporting
confidence: 93%
“…In a substudy of Acute Catheterization and Urgent Intervention Triage strategY (ACUITY) trial, Acharji et al [50] aimed to show the prognostic value of baseline troponin levels of 2179 CKD patients with moderate and high risk of ACS. Of 2179 CKD patients, 1291 had elevated baseline troponin (59.2%).…”
Section: Clinical Studies Of Cad In Ckd Patientsmentioning
confidence: 99%
“…population deserve further study, and should extend beyond the perioperative space. 24 Current guidelines from the American College of Cardiology/American Heart Association advise measuring troponin levels in patients undergoing noncardiac surgery with signs of symptoms of ischemia (Class I recommendation), and both these American College of Cardiology/American Heart Association and the European Society of Cardiology/Heart Association Guidelines give a weak recommendation for routine troponin screening in patients at high risk for perioperative cardiovascular events (Class IIb recommendation). 25,26 While in our study the hazard of mortality was similar in patients not sampled compared to those who were sampled but below the 99th percentile (<0.01 ng/mL), these results are contrary to strong evidence that in the absence of routine troponin sampling, 85% of prognostically important myocardial injuries after noncardiac surgery may be undetected.…”
Section: Discussionmentioning
confidence: 99%